STYX: a versatile pseudophosphatase. (15th April 2017) - Reiterer, Veronika; Pawłowski, Krzysztof; Farhan, Hesso
Abstract : The pseudophosphatase STYX (serine/threonine/tyrosine interacting protein) is a catalytically inactive member of the protein tyrosine phosphatase family. We perform a phylogenetic analysis of STYX and ask how far does the pseudoenzyme status of STYX reaches in evolution. Based on our previous work, we use STYX as a showcase to discuss four basic modes of action that any given pseudoenzyme may exert. Our previous work on the effect of STYX on mitogen-activated protein kinase (MAPK) signaling led us to identify two complementary modes of action. On the one hand, STYX competes with active phosphatases for binding to MAPKs. On the other hand, STYX acts as a nuclear anchor for MAPKs, affecting their nucleo-cytoplasmic shuttling. Finally, we discuss our recent work on the regulation of FBXW7 by this pseudophosphatase and how it affects the ubiquitylation and degradation of its substrates. We discuss the biological significance of this regulatory mechanism and use it as an example for the versatility of pseudoenzymes that may divert away from merely regulating their active homologs.